MENGENTASKAN KEMISKINAN DALAM PERSPEKTIF EKONOMI SYARI'AH - M. Shabri Abd. Majid (Faculty of Economics, Universitas Islam Indonesia, 2011)
This study discusses the concept of poverty from an Islamic perspective. It then attempts to propose a holistic strategy to alleviate poverty in Indonesia within the Shari'ah framework. To eradicate poverty, inter alia, Indonesian Muslims should constantly and steadfastly improve their devoutness to the Almighty God. Their daily activities must be always in harmony with the Divine injunctions, the Holy Qur'an and Hadith. The elite groups must compromise and do not monopolize power and wealth in the country. Developmental budget should be proportionately distributed among its citizens. Just economic and democratic political systems which are free from corruption and malpractices must be upheld. The rich Indonesian Muslims must fulfil their rights to the poor by paying zakat (Islamic tax). The ruling government should not be oppressive; the political elites should not take a chance to reap their benefits in the political instability in the country. The just distribution of income should be preserved so that the continuous efforts to alleviate poverty can be easily intensified.